Pengaruh Kompetensi Sumber Daya Manusia dan Pedoman Akuntansi Pesantren terhadap Akuntabilitas Pesantren - Nur Laila Yuliani; Mohamad Zaenal Mustofa (Universitas Muhammadiyah Metro, 2022)
The accountability of Islamic boarding schools is necessary as it can increase the accountability of Islamic boarding schools. This can increase the trust of donators in Islamic boarding schools. This study aims at examining the effect of Human Resource Competence and Islamic Boarding School Accounting Standards on Accountability of Islamic Boarding Schools. The study tested a sample of boarding school administrators in the form of a foundation in Magelang Regency. The number of samples in this study were 48 respondents taken from purposive sampling method. Data were analyzed through descriptive statistical analysis, validity test, reliability test, multiple linear regression, and hypothesis testing. The results of the data analysis show that the competence of human resources and islamic boarding school accounting guidelines have a positive effect on islamic boarding school accountability.